Comparative parallel analysis of RNA ends identifies mRNA substrates of a tRNA splicing endonuclease-initiated mRNA decay pathway - Hurtig, Jennifer E. (Proc Natl Acad Sci U S A, 2021)
Eukaryotes share a conserved messenger RNA (mRNA) decay pathway in which bulk mRNA is degraded by exoribonucleases. In addition, it has become clear that more specialized mRNA decay pathways are initiated by endonucleolytic cleavage at particular sites. The transfer RNA (tRNA) splicing endonuclease (TSEN) has been studied for its ability to remove introns from pre-tRNAs. More recently it has been shown that single amino acid mutations in TSEN cause pontocerebellar hypoplasia. Other recent studies indicate that TSEN has other functions, but the nature of these functions has remained obscure. Here we show that yeast TSEN cleaves a specific subset of mRNAs that encode mitochondrial proteins, and that the cleavage sites are in part determined by their sequence. This provides an explanation for the counterintuitive mitochondrial localization of yeast TSEN. To identify these mRNA target sites, we developed a “comPARE” (comparative parallel analysis of RNA ends) bioinformatic approach that should be easily implemented and widely applicable to the study of endoribonucleases. The similarity of tRNA endonuclease-initiated decay to regulated IRE1-dependent decay of mRNA suggests that mRNA specificity by colocalization may be an important determinant for the degradation of localized mRNAs in a variety of eukaryotic cells.